Synthesis and Structural Views on New Azo Ligand and Its Metal Complexes with Some of their Application - Fadhil, Asmaa Edrees; Abbas, Alyaa Khider (Iraqi Journal of Science, 2023)
In this work,  we presented a study of the structural formula for a new series of complexes with Ag(I), Cu(II), Zn(II), and Cd(II) derived from the guanine azo dye ligand 2-amino-8-((3-hydroxyphenyl)diazinyl)-1,7-dihydro-6H-purin-6-one (HAG), which is investigated using various physicochemical analyses, spectroscopic techniques (FT-IR, U.V-VIS, and 1H NMR), thermogravimetric analysis (TGA). In addition, elemental analyses, magnetic susceptibility, and molar conductance measurements were all stabilized. As well as the mole ratio, stability constant, and Gibbs free energy were studied for all complexes, where they showed high stability and spontaneous synthesis. The Cu(II) complex was suggested to have octahedral stereochemistry, while the Ag(I), Zn(II), and Cd(II) complexes were suggested to have tetrahedral stereochemistry. The ligand has been demonstrated to be a useful acid-base indicator, and it has been shown that the ligand (HAG) and its complexes exhibit high photostability and have various colors that can be used to dye wool materials.